1985
DOI: 10.1111/j.1365-2362.1985.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocreatine content and intracellular pH of calf muscle measured by phosphorus NMR spectroscopy in occlusive arterial disease of the legs

Abstract: Energy metabolism of calf muscle was assessed non-invasively by phosphorus (31P) NMR spectroscopy in eleven patients with symptomatic arterial occlusion and in seven matched controls. Phosphocreatine (PCr) content and pH values decreased during non-ischaemic foot exercise to lower values in severely afflicted patients but in all patients, as a group, they were not significantly decreased compared to controls. In contrast, recovery from ischaemic exercise (arterial occlusion by a tourniquet) demonstrated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…A possible explanation for this difference is that the claudicants in the present study had not totally recov ered from the walking exercise when arterial occlusion started, which may have overestimated V02 at rest, V02 after walking exercise is more increased in claudi cants than in nonclaudicants. This continued oxygen consumption after exercise may be related to the resyn thesis of high-energy phosphates [23], NMR studies have shown a slower resynthesis of phosphocreatine in claudicants than in nonclaudicants [24], This phenome non can also explain the longer 0 2Hb recovery times and the slower resaturation rates in PAOD patients, which supports the hypothesis that 0 2Hb recovery times and the resaturation rates are a function of PCr resynthesis. During walking exercise PAOD patients showed a higher degree of deoxygenation than nonclau dicants.…”
Section: Discussionsupporting
confidence: 71%
“…A possible explanation for this difference is that the claudicants in the present study had not totally recov ered from the walking exercise when arterial occlusion started, which may have overestimated V02 at rest, V02 after walking exercise is more increased in claudi cants than in nonclaudicants. This continued oxygen consumption after exercise may be related to the resyn thesis of high-energy phosphates [23], NMR studies have shown a slower resynthesis of phosphocreatine in claudicants than in nonclaudicants [24], This phenome non can also explain the longer 0 2Hb recovery times and the slower resaturation rates in PAOD patients, which supports the hypothesis that 0 2Hb recovery times and the resaturation rates are a function of PCr resynthesis. During walking exercise PAOD patients showed a higher degree of deoxygenation than nonclau dicants.…”
Section: Discussionsupporting
confidence: 71%
“…It is widely accepted that phosphometabolite ratios (in particular the PCr/Pi and NTP/Pi ratios) are sensitive indices of tissue hypoxia based upon classical biochemical analyses and NMR measurements in a variety of normal tissues subjected to relative oxygen deprivation (33,(36)(37)(38)(39)(40)(41)(42). The present study indicates that the same relationship pertains in tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Longer recovery times in PVD patients compared to healthy volunteers can be explained by slower resynthesis of phosphocreatine in this type of patient. 19 Two other important reasons for the delayed response in PVD patients are probably rigidity and maximal vasodilatation of arterioles and capillaries. The mean time taken to reach 95% of the maximal HbO 2 levels ͑153 s, range 36-405 s͒ was longer than recovery times reported by other studies where it was found to be 81 s 21 or 40 s. 5 Maximal hyperemic response expressed as the percentage of the signal change during arterial occlusion ͑HR͒ could be used as a measure of resaturation and could give some additional information about blood inflow and oxygen delivery to tissue after the release of the occlusion.…”
Section: Discussionmentioning
confidence: 99%